HYPERFINE STRUCTURE MEASUREMENT OF SODIUMA TOMIC-BEAM ORTHOGONALLY WITH DYE LASER R6G - Hussein, Mohammed; Hafidh, Zaidun (Iraqi Journal of Science, 2024)
Sodium atomic beam of limited broadening, of angular divergence of 5.15o wasgenerated to investigate the hyperfine structure of sodium D2 line. R6G dye laserwas orthogonally interact with Na-atomic beam and recording of fluorescence signal(λ=5896Ǻ) showed a hyperfine structure of Na-D2 line of 1.03 GHz.